Constitutive Activation of the Nlrc4 Inflammasome Prevents Hepatic Fibrosis and Promotes Hepatic Regeneration after Partial Hepatectomy - David A. DeSantis; Chih-Wei Ko; Lan Wang; Peter Lee; Colleen M. Croniger (Hindawi Limited, 2015)
TThe molecular mechanisms responsible for the development of hepatic fibrosis are not fully understood. The Nlrc4 inflammasome detects cytosolic presence of bacterial components, activating inflammatory cytokines to facilitate clearance of pathogens and infected cells. We hypothesized that low-grade constitutive activation of the Nlrc4 inflammasome may lead to induced hepatocyte proliferation and prevent the development of hepatic fibrosis. The gene of Nlrc4 contains two single nucleotide polymorphisms (SNPs), one located within the Nlrc4 promoter and one contained within exon 5. These SNPs regulate Nlrc4 gene transcription and activation as measured through gene reporter assays and IL-1β secretion. The 17C-6 mice have increased IL-1β in plasma after chronic carbon tetrachloride (CCl4) administration compared to B6 mice. After two-thirds partial hepatectomy (2/3PH) 17C-6 mice have earlier restoration of liver mass with greater cyclin D1 protein and BrdU incorporation compared to B6 mice at several time points. These data reveal mild constitutive activation of the Nlrc4 inflammasome as the results of two SNPs, which leads to the stimulation of hepatocyte proliferation. The increased liver regeneration induces rapid liver mass recovery after hepatectomy and may prevent the development of hepatotoxin-induced liver fibrosis.